EFEKTIVITAS MEDIA POP-UP BOOK BERBASIS KEARIFAN LOKAL TERHAHADAP MINAT BELAJAR SISWA SD - Nurfadilah Rahmadani; Muh Khaedar; Nurhadifah Amaliyah; A. Alfiani Damayanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effectiveness of local wisdom-based pop-up bookmedia on students learning interests in elementary schools. This study is a Pre-Experiment study using a quantitative approach. This study took place at the UPTSPF SD Inpres Manggala. The sample in this study were all students of class IVB,with a total of 38 students, 17 boys and 21 girls. The sampling technique usedpurposive sampling technique. The data collection method was analyzed usingSPSS Statistics 25, where the teachers activity observation sheet obtained anaverage value of 3.3 which means it was carried out well, then on student activitiesan average value of 3.4 was obtained with a good category. Then the results ofthe inferential analysis showed that the normality test value obtained P-Valuepretest = 0.549 which means it is normally distributed, then the results of thehomogeneity test obtained a P-Value value = 0.371 which means homogeneity ismet. The results of the hypothesis test obtained a value of 0.000 which is smallerthan the significance level of 0.05, which means that there is a difference instudents' learning interest, so H 1 is rejected and H 0 is accepted. So based on theresults of the study, it can be concluded that pop-up book media based on localwisdom is effective for use on students learning interest in elementary school.